(untitled) - Sverdrup, H. U. (New Jersey, 1961)
Contents: The Earth and the ocean basins; Physical properties of sea water; General distribution of temperature, Salinity, and density; Chemistry of sea water; Organisms and the composition of sea water...
Keywords: Oceanography,Hải dương học